PHENOLOGICAL PECULIARITIES OF DEVELOPING AGRILUS CHRYSODERES ON THE PLANTED AREAS OF EUROPEAN BLACK CURRANT IN THE UKRAINE’S POLISSIA - Bakalova, A. V.; Tkalenko, A. M.; Gritsyuk, N. V.; Derechа, O. A.; Shchepanivskyi, D. S. (Scientific Progress & Innovations, 2019)
The article presents the research results of phenological developing Agrilus chrysoderes in currant agro-ecosystem of Polissia, Ukraine. According to the analysis of long-term development dynamics of Agrilus chrysoderes, a phenological calendar was made, which clearly foresees the period of manifesting the great-est harmfulness of this phytophage and it mainly falls on the 2nd – 3d decade of June. According to its bio-logical development Agrilus chrysoderes winters in the larval stage in the plantlets of currant bush and is considered a dangerous hidden-existing pests. During the experiment the transformation of the larva into pupa was observed only in the second half of May. The beetles of new generation 6−8 mm long, greenish in color, appeared in the end of the second decade of May. During 3 years of studying Agrilus chrysoderes no considerable deviations in the phytophage metamorphosis were observed. The phytophage sexual marriage lasted from the third decade of May to the first decade of June. As a result of the research it was proven that the damaging of young current branches with the phytophage resulted in decreasing plant productivity. At the average populating of black currants (4–5 points) with Agrilus chrysoderes the weight of 100 berries of Titania, Suita Kyivska varieties decreases by 1.3 times, Amethyst variety – by 1.2 times, Chereshneva and Chernecha varieties – by 1.4 times. At populating currant plants with Agrilus chrysoderes at 8–9 points, the weight of 100 berries is reduced by 2 to 3 times. The significant negative effect of the phytophage on growing European black currant has lately been one of the most important problems, and the serious damage is mainly made by larvae, reducing the yield under the influence of disturbing the cause of normal physiologi-cal processes in the host plant. As a result of larvae damaging the middle of black currant shoot, the conduc-tive vessels are damaged, which leads to changes in metabolism, causes inhibition of the vascular-conduction system, resulting in the plant growth retarding, decreasing yields, and worsening the quality of berries. It is proved that Agrilus chrysoderes larvae mainly damage the most productive branches (2–3 years) that give the main crop from the bush.